‘Vaccine preferences and government responsiveness in a public health crisis: Lessons from the Middle East’ - Nimah Mazaheri (Global Public Health)
This article examines the causes of vaccine preferences during the COVID-19 pandemic through an analysis of surveys conducted in 11 countries in the Middle East and North Africa (MENA) region. It centres on how an individual’s political ideology and views about the government’s pandemic response influenced preferences about vaccines, specifically the choice to only get a vaccine from a particular supplier (e.g. Pfizer, AstraZeneca, Sinovac, etc.) versus the willingness to get the first available vaccine. The analysis shows that people who are politically engaged and pro-democracy are less likely to hold preferences about vaccine brands compared to democracy skeptics and those who are politically disengaged. Yet, a person’s experiences and interactions with their government during the pandemic critically mattered. People in the MENA region who had negative views of their government’s response to the pandemic and those who did not receive pandemic relief aid were more likely to express a strong preference about vaccine brand. The emergence of distinct preferences about vaccine brands are an understudied but ongoing problem in the global effort to vaccinate people from deadly diseases.